2016
DOI: 10.2139/ssrn.2798048
|View full text |Cite
|
Sign up to set email alerts
|

SPACs: Post-Merger Survival

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The findings also showed that bad acquisitions are driven by contractual features that give SPAC managers incentives to pursue any acquisition over no acquisition in order to avoid the liquidation of the SPAC. This is in line with the findings of Vulanovic (2016Vulanovic ( a & 2016b on post-merger survival, showing that the collection of equity compensation and underwriting fees by stakeholders are dominant motives to approve bad acquisitions. Finally, evidence confirms that SPAC acquisitions significantly underperform various benchmarks from the accounting perspective such as operating margins and return on sales, and the poor operating performance of SPACs does not appear to be caused by higher leverage and financial distress costs (Dimitrova 2017).…”
Section: Literature Reviewsupporting
confidence: 88%
“…The findings also showed that bad acquisitions are driven by contractual features that give SPAC managers incentives to pursue any acquisition over no acquisition in order to avoid the liquidation of the SPAC. This is in line with the findings of Vulanovic (2016Vulanovic ( a & 2016b on post-merger survival, showing that the collection of equity compensation and underwriting fees by stakeholders are dominant motives to approve bad acquisitions. Finally, evidence confirms that SPAC acquisitions significantly underperform various benchmarks from the accounting perspective such as operating margins and return on sales, and the poor operating performance of SPACs does not appear to be caused by higher leverage and financial distress costs (Dimitrova 2017).…”
Section: Literature Reviewsupporting
confidence: 88%
“…SPACs, on the other hand, drastically underperform ordinary IPOs in terms of performance and, as a result, are not value-creating investments. (Kolb 2016) Vulanovic (2016) investigates how structural factors and contract sets which generates invectives for the SPACs affect their survival after the merger is completed.He discovers that SPACs' structural characteristics are essential in predicting post-merger results. The paper highlighted that SPAC management and underwriters' pre-merger commitment, as well as early favorable market performance, boosts the chance of survival after merger.Whereas, the risk of failure is more when there is high transaction cost and the focus is on the overseas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although SPACs are taking an essential share of the IPO market, the phenomenon has not yet been fully explored. Previous studies have focused on the unique structure and features of SPACs Lakicevic et al [ 1 ], Chatterjee et al [ 2 ], Boyer and Baigent [ 3 ], Okutan Nilsson [ 4 ], Cumming et al [ 5 ], and Vulanovic [ 6 ]. Other studies have investigated the performance of SPACs in various market conditions (for example: Kolb and Tykvova [ 7 ], and Dimitrova [ 8 ]).…”
Section: Literature Reviewmentioning
confidence: 99%